Defining the patterns of change in PM2.5 concentrations in Kyiv under military load based on scenario analysis - Hnatiuk, Viacheslav; Skliarova, Anastasiia; Kyrylenko, Yuliia; Sidorov, Dmytro; Shabliy, Tetyana (Eastern-European Journal of Enterprise Technologies, 2026)
This study examines the process of formation and change of the atmospheric air state over an urbanized territory under conditions of military-technogenic load. The task addressed is to define features in the spatial-temporal dynamics of PM2.5 concentrations under the influence of military load on urbanized territories. The work has assessed the impact of massive air attacks on the state of the atmospheric air in the city of Kyiv in 2025 based on the fine PM2.5 particles concentrations. The study used data from air quality monitoring networks aggregated at the SaveEcoBot platform (Ukraine), as well as information on the nature, intensity, and consequences of military events in the capital's districts. An integrated scenario approach to assessing the relationship between shelling and changes in PM2.5 concentrations has been proposed, based on a combination of spatial, temporal, and event characteristics. The methodology takes into account the background values of PM2.5 concentrations for each district, as well as the type of local impact of military events. Within the model, scenarios of direct and indirect impact, deterioration of air quality without shelling, situations without a significant increase in PM2.5 and control cases were distinguished. It was established that the largest share of observations (80.2%) is made up of cases of possible indirect impact – 340 episodes associated with the transfer of combustion products from the fire site and secondary aerosol pollution. For the category of direct possible impact, 28 cases (6.6%) were recorded at the highest average value of the integrated index of 0.79, which corresponds to a high level of connection between military events and deterioration of air quality. It has been shown that military events form short-term periods of extreme atmospheric air pollution. The results of the study lay the groundwork for further integrated assessment of the combined impact of atmospheric, technogenic, and military factors on urbanized areas